Conceptualization, Characterization and Establishment of Model Large Cardamom Village in Eastern Himalaya of West Bengal (Indian Journal of Extension Education, 2024)
The farmers’ livelihood in the Himalayan region of West Bengal mainly depends on large cardamom cultivation. However, the farmers in the region were continuously facing low yield, high disease incidence, and poor quality of large cardamom. An alternative extension approach namely ‘Model Large Cardamom Village’ was conceptualized to address these issues in Tindhurey village of Kalimpong in West Bengal. Diverse scientific technologies and practices were promoted in the adopted village from 2018 to 2022. An outcome-based impact evaluation was done in 2023 with a sample of 350 farmers. The maximum yield increment was observed in the Seremna cultivar (45.94%) followed by Bharlangey (42.86%), Ramsai (40%), and Golsey cultivar (36.67%). Similarly, the maximum increase in income was reported in the Seremna cultivar from Rs. 160000/ha. to Rs. 290000/ha. Other significant impact of Model Large Cardamom Village was increased adoption of recommended technologies, the decline in pest and disease incidence, enhanced social networking, the decline in migration of youth from the village, increased access to different production inputs and services, and starting large cardamom-based tourism. The study shows the potential of a specific and focused extension approach to address the technological gap at the regional level.